PERLINDUNGAN HUKUM PRODUK SKINCARE MELALUI PENGGUNAAN MEREK HOLOGRAM: PERSPEKTIF KEKAYAAN INTELEKTUAL - Permatasari, Putu Ayu Intan Widya; Samsithawrati, Putu Aras (Kertha Negara : Journal Ilmu Hukum, 2024)
The purpose of this research is to understand and analyze the functions of brands, especially hologram brands, particularly in the skincare product context, from the perspective of intellectual property and the legal steps involved in the first-to-file registration system to protect skincare products in relation to the use of hologram brands from an intellectual property perspective. The research method used is normative legal research with legislative, conceptual, and analytical approaches. The results of the research indicate that the function of brands, especially hologram brands in connection with skincare products from an intellectual property perspective, is to distinguish goods produced by one company from similar goods produced by other companies. Specifically, hologram brands have a more specific function where optical information forms an image or scene. Holograms represent the latest form of information storage. Referring to the legal protection system for brands, which is the first-to-file system, the legal step of brand registration is mandatory to protect skincare products concerning the use of hologram brands from an intellectual property perspective.